ТОПЫРАҚТЫҢ ЭЛЕМЕНТЛИК ҚУРАМЫНА МӘДЕНИЙ ЕГИНЛЕРДИҢ ТӘСИРИ - Жумамуратов, А.; Жумамуратов, М.А.; Сыдиков, И.М. (ILIM hám JÁMIYET, 2017)
The article is devoted to the study of changes in the microelements of soil when growing the cultural plants by the method of neutron-activational analysis.